The Meaning of Faqir in the Perspective of Sufism Imam Qusyairi An Naisaburi Therapeutic Study of Stress Diseases - Septa Monika; Wijaya; Heni Indrayani (Universitas Muhammadiyah Palu, 2025)
Faqir is generally a word used to describe the state of society, where people are unable to meet their daily needs. Thus, the word faqir can be interpreted as a general understanding of a person or a society that cannot improve its standard of living because it cannot meet the needs of resources in its life. Stress is the body's reaction or response to psychological stressors (mental stress or life stress). Stress is a person's non-specific response to a need that exists in him. People who experience stress may behave differently than those who don't. This study aims to find out how faqir according to the perspective of Imam Al Qusyairi An Naisaburi in the book Risalah Qusyairiyah and find out how the meaning of faqir can be a therapy for stress diseases. This research is a qualitative research that focuses on literature studies. In this study, data is sourced from several sources such as in the book